Synthesis and photocatalytic activity of nanocrystalline ErMnO3 by microwave assisted process. (19th May 2018) - Min, Jiayuan; Tang, Peisong; Xie, Xinyu; Xu, Yunyi; Chen, Haifeng; Yu, Longlong
ABSTRACT: The single phase ErMnO3 nanoparticles were synthesized by microwave process and high temperature calcination. The structure and morphology of prepared ErMnO3 were characterized by thermogravimetry and differential scanning calorimetry (TG-DSC), powder X-ray diffraction (XRD), Fourier transform infrared spectroscopy(FT-IR) and scanning electron microscopy (SEM). It was found that the single phase ErMnO3 can be obtained through calcination the microwave prepared ErMnO3 precursor at 1050°C. And the resulting product had an average particle size of around 80 nm. The ErMnO3 sample calcined at 1050°C showed high photocatalytic activity for decomposition of methyl orange under ultraviolet light irradiation. The ErMnO3 sample was in line with first-order kinetic model for the degradation of methyl orange. And the apparent rate constant was 0.019 min −1 .